Orientación familiar en la enseñanza de habilidades para la vida diaria de las personas con discapacidad intelectual del CDDI MIES - Loja, 2024 - Cochancela Coronel, Nahomi Sarai (2025)
The families that have a member with an intellectual disability, when receiving family orientation, find it very significant to achieve the teaching of daily living skills, from this research point of view, it is necessary to train and orient the family for the teaching of these skills. The objective was to analyze the influence of family orientation in the teaching of daily living skills in people with intellectual disabilities in the day center of integral development MIES - Loja, for which a sample of ten parents and/or representatives and ten people with intellectual disabilities were taken into account. In the collection of information, the scientific method facilitated the veracity of the information, and the following techniques were used: observation and survey. The triangulation of data and techniques allowed asserting that families do not know about the teaching of daily life skills, so that the research reveals the skills that users have not acquired such as risk prevention in the home: detecting a gas or water leak, money management, and community activities: use of means of transportation and those that are in the process of acquisition such as hygiene and personal care: nail cutting; domestic skills: care of personal space; autonomy in eating: food preparation, knowledge and use of free time: playing sports. The design of a proposal of activities called “A shared path: educating families for the development of daily living skills” is proposed, taking as a reference the results obtained in the research